The impact of mergers and acquisitions on technological innovation in state-owned enterprises: The moderating role of mixed-ownership - Niannian Wu; Furong Guo; Bingxia Wang (PLoS ONE, 2025)
Using data from Chinese A-share listed state-owned enterprises (SOEs) between 2007 and 2019, we examine how mergers and acquisitions (M&As) affect SOE innovation through patent outputs, with a focus on mixed-ownership M&As where SOEs acquire private firms. Our results show that while M&As generally enhance SOE innovation through increased patent applications, mixed-ownership M&As demonstrate significantly stronger positive effects compared to SOE-to-SOE M&As. This enhancement is most notable when control rights are transferred, when acquiring SOEs possess high R&D investment but lower production efficiency, and in regions with less developed markets. The primary mechanism appears to be improved corporate governance through increased private shareholder involvement in strategic decision-making. These findings advance our understanding of how ownership differences influence innovation in M&As while providing practical guidance for SOE reform policies in China and similar emerging economies.